Seasonal Variability of Forces Controlling Sedimentation in the Sundarbans National Forest, Bangladesh - Hale, R. P.; Wilson, C. A.; Bomer, E. J. (Frontiers in Earth Science, 2019)
Southwest Bangladesh, located on the Ganges-Brahmaputra-Meghna delta, is experiencing the impacts of sea level rise (SLR) due to processes at both the local and global scale. In particular, regional alterations of the hydrodynamic network due to embankment construction has drastically altered effective SLR, placing millions of inhabitants at risk of prolonged inundation, and threatening the world’s largest continuous mangrove stand, the Sundarbans National Forest (SNF). In order to effectively employ landscape recovery solutions, an understanding of local sediment transport and deposition is critical. This field-based study investigates the sediment dynamics between the mangrove platform and tidal channels of the SNF using data from a variety of instruments and sediment samples collected within a forested sub-basin (~20 km2) fed by a major tidal channel. We observe profound seasonal variability within the sub-basin, with the wet season exhibiting deeper and longer inundation of the mangrove platform and greater suspended sediment concentrations (SSC). Further, there exists a trend of decreasing SSC and median grain size from the perimeter of the SNF to the interior, and decreasing SSC from the tidal channel to the platform at both locations. We project seasonal platform sedimentation rates ranging from 0.17 ±0.16 cm in the dry season to 1.8 ± 0.35 cm in the wet season. Importantly, the annual deposition rate measured at either location is sufficiently rapid to keep pace with observed rates of effective SLR published in other studies (~1.0-1.7 cm/yr). Based on our results, it appears that many controls on sedimentation are both covariant and of similar importance to land aggradation in the SNF. While inundation depth and frequency will likely increase under future SLR scenarios, sediment supply is threatened by India’s proposed River Linking Project, which could decrease the sediment loads of the Ganges and Brahmaputra Rivers by as much as 75% and 25%, respectively. These rivers provide the sediment for the entire delta, and we predict that with decreasing SSC, some regions—particularly interior sediment depleted regions—may begin to deteriorate and become submerged, including within the SNF.